When and how do elite soccer players sprint in match play? A longitudinal study in a professional soccer league - Oliva-Lozano, J. M.; Fortes, V.; Muyor, J. M. (Research in Sports Medicine, 2023)
The aims of this study were to examine the periods in which the maximum speed actions occurred during elite soccer matches and analyse these actions considering the effect of playing position and different contextual variables. Performance-related variables (VMAX: maximum speed; Vo: starting speed; SPD: sprinting distance; ACCMAX: maximum acceleration; DECMAX: maximum deceleration) and sprint-related contextual variables (trajectory, ball possession, role, field area in which the action occurred) from each maximum speed action were collected. The first 15 minutes of each match half elicited most maximum speed actions (44.6% of cases), regardless of playing position (likelihood ratio, LR=13.95; p=0.95). However, playing position had a significant effect on the role of the action (Chi-Squared, ?2=50.68; p=0.001) and the field area in which the sprint occurred (?2=26.54; p=0.001). Regarding the effect of different contextual variables on the sprint-related performance variables, no significant effect from any contextual variable on ACCMAX, DECMAX or Vo was found (p > 0.05). Nevertheless, the contextual variables had a significant effect on SPD (from ball possession: sprints without ball > sprints with ball; trajectory: non-linear sprints > linear sprints; role: offensive sprints > defensive sprints) and VMAX (from ball possession: sprints without ball > sprints with ball; playing position: midfielders < other positions).